Morphological spectrum and molecular features of somatic malignant transformation in germ cell tumours. Issue 1 (5th May 2022) - Lobo, João; Rodrigues, Ângelo; Henrique, Rui; Christiansen, Ailsa; Beyer, Jörg; Moch, Holger; Bode, Peter Karl
Abstract: Aims: Somatic malignant transformation (SMT) arising in germ cell tumours (GCTs) is an infrequent, but clinically relevant event. There is only limited knowledge on the morphological spectrum of SMT, and the therapeutic management of these patients is poorly defined. In this work we revisit two consecutive case series ( n  = 756) of GCTs. Clinicopathological data of SMTs arising in GCTs were determined, with a focus on the histopathological spectrum, and molecular aspects were obtained by Fluorescence in situ Hybridization (FISH) and Next Generation Sequencing (NGS). Methods and Results: Thirty male patients (28 primary testicular, two primary extragonadal) were included. These patients represent 4% of GCT patients diagnosed at two institutes (University Hospital Zurich and IPO Porto). The most common SMTs were adenocarcinoma ( n  = 8), embryonic‐type neuroectodermal tumours (ENETs, n  = 8), and rhabdomyosarcoma ( n  = 6), but a wide range of challenging morphologies were depicted, including low‐grade neuroglial tumour, adenosquamous carcinoma, neuroblastoma, and neuroendocrine carcinoma. SMT was found in 15 primary tumour samples and in 27 metastatic samples of these 30 patients, the latter showing poorer overall survival. Adenocarcinoma occurred only in metastasis postchemotherapy and in one primary retroperitoneal GCT with SMT, but not in GCT of the testis. The 12p gains were identified by FISH in all cases. NGS results were available in six patients. Clinical trials and/or targeted treatments based on the molecular profile of SMT were recommended in four patients. Conclusions: SMT arising in GCTs represent a diagnostic challenge and should be confirmed by a specialized uropathologist. NGS‐based treatment recommendations may improve the outcome of these patients. Abstract : Somatic malignant transformation (SMT) occurred in 4% of germ cell tumour (GCT) patients, with most common histologies being adenocarcinoma, embryonic‐type neuroectodermal tumour (ENET) and rhabdomyosarcoma, but a wide range of morphologies was seen. Patients with evidence of SMT in the metastatic mass showed significantly poorer overall‐survival compared to those with SMT exclusively in the primary testicular tumour. Clinical trials and targeted treatments based on molecular profile assessed by NGS were recommended in 4 patients.